2017
DOI: 10.1007/s11136-017-1614-5
|View full text |Cite
|
Sign up to set email alerts
|

Establishing benchmark EQ-5D-3L population health state utilities and identifying their correlates in Gansu Province, China

Abstract: This study reports HSUs for a Chinese population in Gansu and investigates the key correlates of HSUs in this population. In addition, the use of EQ-5D-3L in assessing population health is limited given the high ceiling effect and skewed HSUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 79 publications
3
11
1
Order By: Relevance
“…In respondents with chronic diseases, anxiety/depression was the dimension that was most affected. This result is consistent with the long-term detrimental impact on HRQOL for the population with chronic diseases, especially for mental health among the comorbidity population [51,52]. Therefore, programs for the poverty-stricken population with chronic diseases should place greater emphasis on psychological health.…”
Section: Heterogeneous Effectssupporting
confidence: 79%
See 1 more Smart Citation
“…In respondents with chronic diseases, anxiety/depression was the dimension that was most affected. This result is consistent with the long-term detrimental impact on HRQOL for the population with chronic diseases, especially for mental health among the comorbidity population [51,52]. Therefore, programs for the poverty-stricken population with chronic diseases should place greater emphasis on psychological health.…”
Section: Heterogeneous Effectssupporting
confidence: 79%
“…Therefore, programs for the poverty-stricken population with chronic diseases should place greater emphasis on psychological health. Third, married subjects and respondents with high educational attainment were associated with high health utility scores [52,53]. A study in Vietnam showed that women tend to suffer more problems in terms of pain/discomfort and anxiety/depression and have a lower overall HRQOL than men [24].…”
Section: Heterogeneous Effectsmentioning
confidence: 98%
“…utility decrement in cancer stage I-IV patients all exceeded the minimally important difference (0.074) of EQ-5D-3L (Si, Shi, Chen, & Palmer, 2017;Walters & Brazier, 2005). As expected, larger magnitudes on utility decrement were found in patients with a more severe stage of gastric cancer.…”
Section: F I G U R E 2 Decrements On the Eq-5dsupporting
confidence: 69%
“…The mean EQ‐5D utility score (2014/2018 tariff) of high‐grade intraepithelial neoplasia/CIS, stage I, stage II, stage III and stage IV cancer patients was 0.077/0.039, 0.254/0.121, 0.249/0.123, 0.353/0.182 and 0.591/0.309 lower than controls respectively. Except for high‐grade intraepithelial neoplasia/CIS, the mean EQ‐5D utility decrement in cancer stage I‐IV patients all exceeded the minimally important difference (0.074) of EQ‐5D‐3L (Si, Shi, Chen, & Palmer, 2017; Walters & Brazier, 2005). As expected, larger magnitudes on utility decrement were found in patients with a more severe stage of gastric cancer.…”
Section: Discussionmentioning
confidence: 95%
“…QALYs of individual subjects were calculated according to the time spent in different health states and the health utilities assigned to these states based on Chinese preferences (Table 1). For individuals with NPG, utilities value were determined as those of the general population at corresponding ages, and the time duration of utility was considered for the population according to the number of years with diabetes [21]. The utility value was adjusted as 99.08% of NPG [20].…”
Section: Discussionmentioning
confidence: 99%